Congress wort analysis from commercial buckwheat malt mixtures with RSM - Podeszwa, Tomasz; Harasym, Joanna; Czerniecki, Piotr; Kopacz, Magdalena (Engineering Sciences And Technologies, 2016)
The rising prevalence of allergic or intolerance responses for food containing specific cereals or their derivatives such as wheat, barley or rye has resulted in intense scientific research focused on providing gluten-free raw materials and products. As beer is mainly made from barley or wheat malt, this problem also appears in the brewing industry. The removal of harmful protein and the usage of gluten-free raw material are the two most typical routes to avoid gluten presence in beer. A raw material with great potential in brewing is buckwheat, which as a pseudocereal does not contain any gluten allergenic proteins. Although the scientific work has not so far led to brewing beer from 100% buckwheat malt without enzyme addition support – this raw material is still undergoing extensive investigation. However commercial buckwheat malts have appeared on the market, which the producers declare suitable for brewing. In this study Château Buckwheat (Castle Malting) commercial buckwheat malt was evaluated for its suitability for brewing. Malt grain analysis and the influence of buckwheat malt contribution in malt mixture on extract yield, viscosity and colour of congress worts were evaluated using RSM
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2016, Nr 3 (22), s. 77-89
Keywords: buckwheat malt; beer; congress mash; Castle Malting; RSM; słód gryczany; piwo; brzeczka kongresowa